Musicological Study: Analysis of Laras Ganda in The Song “Angin” by Mang Koko - Maulana, Marsel Ridky; Saputra , Raffa Arya; Sutisna , Diynan Prayuga; Kartono P, Alfin Pradinata (Universitas Negeri Medan, 2025)
Mang Koko's song “Angin” represents an innovation in Sundanese karawitan that develops a creative and innovative application of laras ganda. This study aims to explore the application of laras ganda, namely the combination of laras salendro and laras madenda in the composition and analyze its impact on the musical dimension and artistic expression. Using a content analysis method based on a qualitative approach, this research utilizes data in the form of sheet music and audio recordings as the main study material. The results of the analysis show that the use of laras ganda in the song “Angin” is systematically designed to present a harmonious and profound transition of atmosphere. The alternation between laras not only enriches the complexity of the musical structure but also strengthens the aesthetic appeal and emotional narrative of the song. This reflects Mang Koko's ability to combine traditional values with musical innovation, making this work relevant in various cultural contexts, both traditional and modern. Thus the laras ganda in the song “Angin” functions as a key aspect in creating a unique diversity of musical colors while affirming the position of Sundanese karawitan as a dynamic, adaptive and progressive art in facing the challenges of the times.